Evolution of surgical treatment for breast cancer - V. P. Letyagin (Опухоли женской репродуктивной системы)
The paper considers main surgical interventions used to treat breast cancer. It defines the role and place of conservative surgery and describes current procedures for the organ-saving treatment of cancer at this site.